2019
DOI: 10.1007/s10826-019-01581-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of the Enhancing Parenting Skills Programme

Abstract: Objectives This study reports on the feasibility and initial effectiveness of an individually delivered parent programme for parents of young children with behaviour problems. Whilst parenting programmes are known to be effective in reducing behaviour problems, numerous barriers can prevent families from accessing programmes. Individually delivered parent programmes may be more accessible. In the UK, health visitors provide support to all families with a child under 5 years of age and are ideally placed to del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…This approach recruited four parents in each school. Parenting programs do not always reach the families who could most benefit, and collaborative approaches are needed to ensure that families most likely to benefit are recruited (Williams et al, 2020). The results from this trial showed that using a proactive approach, targeting and contacting those whose children were considered most in need, produced successful recruitment of families of children for whom both the school and parents had concerns.…”
Section: Discussionmentioning
confidence: 96%
“…This approach recruited four parents in each school. Parenting programs do not always reach the families who could most benefit, and collaborative approaches are needed to ensure that families most likely to benefit are recruited (Williams et al, 2020). The results from this trial showed that using a proactive approach, targeting and contacting those whose children were considered most in need, produced successful recruitment of families of children for whom both the school and parents had concerns.…”
Section: Discussionmentioning
confidence: 96%
“…The DPICS was designed to assess the quality of parent–child interaction and has high inter-rater reliability for both parent and child behaviors ( Robinson and Eyberg, 1981 ). The DPICS has been extensively used in parenting research ( Hutchings et al, 2007 ; Williams et al, 2020 ). The following skills were coded: praise, direct (clear) commands, indirect (vague) commands, questions, and negative parenting (comprised of negative commands and critical statements).…”
Section: Methodsmentioning
confidence: 99%